Synthesis of nanoporous carbonaceous materials at lower temperatures - Liping Zhang; Alexandre A. S. Gonçalves; Mietek Jaroniec (Frontiers in Chemistry, 2023)
Nanoporous carbonaceous materials are ideal ingredients in various industrial products due to their large specific surface area. They are typically prepared by post-synthesis activation and templating methods. Both methods require the input of large amounts of energy to sustain thermal treatment at high temperatures (typically >600°C), which is clearly in violation of the green-chemistry principles. To avoid this issue, other strategies have been developed for the synthesis of carbonaceous materials at lower temperatures (<600°C). This mini review is focused on three strategies suitable for processing carbons at lower temperatures, namely, hydrothermal carbonization, in situ hard templating method, and mechanically induced self-sustaining reaction. Typical procedures of these strategies are demonstrated by using recently reported examples. At the end, some problems associated with the strategies and potential solutions are discussed.